2022
DOI: 10.3390/su142113975
|View full text |Cite
|
Sign up to set email alerts
|

The Spatial Disequilibrium and Dynamic Evolution of the Net Agriculture Carbon Effect in China

Abstract: Considering the comparative perspective of the net agricultural carbon effect in China’s three major functional grain production areas, the Dagum Gini coefficient, kernel density estimation and Markov chain analysis are used to investigate the spatial disequilibrium and dynamic evolution characteristics of the net agricultural carbon effect in China from 2000 to 2019. The results show that the overall net agricultural carbon sink in China is on a fluctuating upward trend, and the net agricultural carbon sink i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 43 publications
0
0
0
Order By: Relevance
“…Using spatial analysis tools, the transition process between different levels of drought resistance capacity as reflected in the research units was quantitatively calculated in a transition matrix, as shown in Table 5 (where the rows in the transition matrix represent drought resistance capacity levels based on the fuzzy evaluation method, and the columns represent levels based on the supply-demand balance method). The elements on the diagonal of the state transition probability matrix represent the probability of transition between the same levels using both methods, while the off-diagonal elements represent the probability of transitioning between different levels [47,48]. Table 5 shows that in the low-level transitions, the probability values on the diagonal are greater than the off-diagonal probability values, indicating some stability between these levels.…”
Section: Rationality Analysismentioning
confidence: 99%
“…Using spatial analysis tools, the transition process between different levels of drought resistance capacity as reflected in the research units was quantitatively calculated in a transition matrix, as shown in Table 5 (where the rows in the transition matrix represent drought resistance capacity levels based on the fuzzy evaluation method, and the columns represent levels based on the supply-demand balance method). The elements on the diagonal of the state transition probability matrix represent the probability of transition between the same levels using both methods, while the off-diagonal elements represent the probability of transitioning between different levels [47,48]. Table 5 shows that in the low-level transitions, the probability values on the diagonal are greater than the off-diagonal probability values, indicating some stability between these levels.…”
Section: Rationality Analysismentioning
confidence: 99%
“…where h denotes the search radius, (x − x i ) 2 + (y − y i ) 2 denotes the distance from the estimated point X to the ith point and n is the total number of ecological farms [51].…”
Section: Kernel Density Analysismentioning
confidence: 99%
“…To achieve the "dual-carbon" goal, scholars have conducted systematic research on the carbon effects of farmland. Currently, the research mainly focuses on the following areas: (1) estimation and analysis of carbon emissions and carbon uptake on farmland at the national or regional level, such as Dioha estimated the total greenhouse gas emissions from the Nigerian agriculture sector [11], Hemingway estimated the greenhouse gas emissions from crops in an Indian village [12], Li calculated the carbon emissions and carbon uptakes on the Qinghai-Tibet Plateau in China [13], and Dyer assessed energy-based greenhouse gas emissions from Canadian agriculture [14]; (2) factors influencing carbon effects on farmland, such as agricultural inputs [15,16], land-use changes [17,18], planting and cultivation patterns [19,20], and straw return [21], and driving mechanisms of carbon emissions in farmland, including agricultural technology [22], national policies [23], and markets [24]; (3) predictions of carbon emissions by grey prediction models [25,26], neural networks [27,28], the STIRPAT model [29], and estimations of carbon-emissions reduction potential [30]; and (4) carbon-uptake enhancement and emissions-reduction pathways and policies, including integrated crop-livestock systems [31], organic farming [32], conservation tillage [33,34], intermittent water-saving irrigation, agricultural investments [35], and a series of policy recommendations [36].…”
Section: Introductionmentioning
confidence: 99%